CORPORATE GOVERNANCE AND VOLUNTARY HUMAN CAPITAL DISCLOSURE IN THE LISTED COMPANIES OF BANGLADESH: A CONCEPTUAL OVERVIEW - Shamem Ara Mili; Fathyah Hashim (International Journal of Accounting, Finance and Business, 2020)
Human capital disclosure provides information on companies’ human capital development initiatives, employees’ current benefits, and their future safety. Higher level of human capital (HC) disclosure might be able to make the employees more pleased and motivated. However, good corporate governance (CG) makes sure professional ethics in business, and functions in favour of the interest of diverse stakeholders of the business. HC disclosure is voluntary in Bangladesh, and hence, corporate governance mechanisms (CGMs) could play an important role to disclose more HC information. Similarly, from the agency theory standpoint, HC disclosures reduce information asymmetry, and thus, HC disclosures could minimize the agency conflicts associated with the business. The aim of the paper is to integrate pertinent empirical researches and literature to extend the potentials of CG attributes to amplify HC disclosures of the listed firms in Bangladesh. In addition, the paper will present theoretical base for future empirical investigation to expand the agency theory explanation regarding the association of CG with HC disclosures. Moreover, extant literature provides inconsistent and less evidence regarding the rapport of CG with HC disclosures. The present paper recommends and illustrates potential propositions for future empirical study. It is expected that the empirical investigations on these propositions would endow with knowledge to investors, practitioners, and policy makers regarding upgrading voluntary HC disclosure by means of superior corporate governance.